Problematics in the Implementation of Religious Court Decisions on the Execution of Child Support after Divorce - Rahayu, Yunita Sri; Yul, Widiya (Dinasti Research, 2025)
This study examines the problems surrounding the implementation of Religious Court decisions related to the execution of child support obligations following divorce, focusing on three court rulings: Decision No. 180/Pdt.G/2025/PA.Spn, Decision No. 405/Pdt.G/2024/PA.Spn, and Decision No. 408/Pdt.G/2024/PA.Spn. The primary objective of this research is to assess the effectiveness of the implementation of these decisions in practice and to identify factors that hinder the fulfillment of children’s rights after divorce. The research employs a qualitative method with an empirical juridical approach, conducted through document analysis of decisions issued by the Sungai Penuh Religious Court, observation of the substance of the rulings, and examination of legal, economic, and social aspects influencing their implementation. The findings indicate that the execution of child support decisions continues to face significant challenges. From a legal perspective, weak enforcement mechanisms and low compliance by fathers with court decisions constitute major obstacles. Economically, disparities in fathers’ financial capacity contribute to delays or inability to fulfill child support obligations. Socially, low parental awareness following divorce often results in the neglect of children’s rights. Nevertheless, the Religious Court has undertaken efforts to enhance the effectiveness of decision implementation through mediation, the issuance of more realistic and enforceable rulings, and monitoring of compliance. This study recommends strengthening legal enforcement mechanisms, increasing public legal awareness, and developing policies that prioritize the best interests of the child in order to achieve optimal justice and child welfare after divorce.